GAMBARAN STIGMA PADA PROGRAM KERJA WARGA PEDULI AIDS/WPA TERHADAP PEKERJA SEKSUAL (STUDI PADA WPA X DI KOTA SEMARANG) - Naura Afifah Mujoko; Besar Tirto Husodo; Syamsulhuda Budi Musthofa (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
The group formed by the government as community participation in order to ward off the HIV/AIDS called Warga Peduli AIDS/WPA (literary means local residents concerned about AIDS). One of the objectives of this strategy is that no more stigma which hampers HIV/AIDS prevention, PLWHA status in X village is not open yet, but WPA as the main exertion of HIV/AIDS prevention is not expected to have a stigma on the high-risk group. This qualitative descriptive research used a purposive sampling method in determining research subject which are 7 WPA members. The data were taken from in-depth interviews. The validity test in this research were conducted on 3 triangulation subjects such as AIDS Commissions (KPA), the risk group which are sexual worker and public health center. The reliability test is done by auditing data to determine the suitability of research, with look at the focus of research, determining research subjects, collecting research data, analyzing data, testing validity with triangulation subjects, and making research conclusions, and make sure that question is asked several time get a same answer from subject. The results showed that in the planning and the implementation of WPA program, the stigma and discrimination in WPA members were still found, and must be reduced because WPA as community participation in order to ward off the HIV/AIDS. The forms of stigma is the presumption of sexual workers are not devout, even though religiosity is a side that shown to family and God only, intentionally transmitting diseases because of spite with not using condom and not want to be checked if they feel sick, differing in how they dress, ethics, words, and it making presumption that sexual worker hard to be approached.